A bulletproof composite armor and preparation method thereof

By using modified basalt fibers and composite adhesives in bulletproof ceramic composite armor, the mechanical properties and interlayer bonding force of the ceramic surface layer are improved, and the problem of insufficient protection effect of existing bulletproof armor is solved, and excellent protective performance and stability are achieved.

CN119617979BActive Publication Date: 2025-04-18SHANGHAI KAIFU PROTECTION TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510156759.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-18
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

The structural density of the existing bulletproof ceramic composite armor is insufficient, resulting in room for improvement in the protection effect, and the effect of the adhesive is limited, affecting the interlayer bonding force and protective performance.

Method used

The ceramic surface layer with boron carbide as the main component is added, modified basalt fibers and composite adhesive composed of phenolic resin and silicon sol are added. Through high-temperature hot press sintering and hot pressing composite technology, the mechanical properties and interlayer binding force of the ceramic are enhanced.

Benefits of technology

It significantly improves the hardness, bending strength and toughness of the ceramic surface layer, enhances the protective performance of bulletproof composite armor, and can effectively withstand the attack of 3 rounds of 54 12.7mm armor-piercing incendiary bombs, and the depression depth of the back surface layer is less than 10mm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of composite materials, and specifically relates to a bulletproof composite armor and a preparation method thereof. The bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stopping layer and a back-projectile surface layer; the ceramic bullet-facing surface layer is made by high-temperature hot pressing and sintering of 60-70 parts by weight of boron carbide, 15-20 parts by weight of silicon carbide, 8-10 parts by weight of modified basalt fiber, and 2-4 parts by weight of a composite binder; the intermediate crack-stopping layer is an aramid III crack-stopping cloth, and the back-projectile surface layer is an ultra-high molecular weight polyethylene UD cloth, and the layers are bonded by a composite adhesive composed of an epoxy resin and a silica sol. The bulletproof composite armor prepared by the present invention has good low-temperature, high-temperature and wet-heat stability, can adapt to different environmental conditions, has excellent protective performance, and meets the requirements of armor-piercing incendiary bomb protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a bulletproof composite armor and a preparation method thereof. Background Art

[0002] Bulletproof armor is a kind of protective equipment used to protect personnel or vehicles from firearms, shells, explosives or fragments. Its principle is mainly to absorb and disperse the energy from external attacking warheads and fragments to prevent penetration, thereby effectively protecting the personnel or equipment inside. The materials of bulletproof armor are mainly divided into ceramic materials, metal materials and fiber materials. Among them, ceramic materials such as boron carbide and boron nitride have high strength, hardness and rigidity, and can effectively resist the impact of bullets or explosive fragments. However, ceramic materials have poor plasticity and high brittleness, and the protective effect is poor when used alone for protective armor. ; Metal materials such as steel plates and titanium alloys have high strength and toughness and excellent resistance to high-speed projectile penetration. However, due to their thickness, metal materials reduce the user's mobility and limit their application in bulletproof armor. Fiber materials are materials made of high molecular polymer fibers, such as aramid and nylon, which have high strength and toughness, can effectively absorb and disperse energy, and can also be woven into a mesh structure to increase its defensive performance. In order to reduce the weight of protected personnel or equipment and improve the protective effect of bulletproof armor, bulletproof armor materials are gradually being strengthened and lightweight.

[0003] The Chinese patent application with application number CN202010213417.1 discloses a bulletproof ceramic composite armor and a preparation method thereof. First, several layers of ultra-high molecular weight polyethylene film are tightly wound on the bulletproof ceramic plate, and pressed to form a ceramic PE composite unit A with a PE film layer; then the composite unit A is stacked to the designed number of layers, and is stacked with the ultra-high molecular weight polyethylene plate back plate to form a ceramic PE composite module B, which is pressed and formed at high temperature to form a bulletproof ceramic composite armor. The bulletproof ceramic plate is made of aluminum oxide, zirconium oxide, silicon carbide, boron carbide, boron nitride or silicon nitride, but the compatibility between the bulletproof ceramic plate made of inorganic materials and the ultra-high molecular weight polyethylene film is poor, which makes the structural density of the bulletproof ceramic composite armor insufficient, and its protective effect has room for improvement; the application number is CN202010213417.1. Chinese patent No. 0012520.X discloses a bulletproof composite armor and a preparation method thereof, wherein a composite ceramic plate, an aramid fiber cloth, and an ultra-high molecular weight polyethylene back plate are hot-pressed and composited in a high-temperature autoclave to obtain a bulletproof composite armor, wherein the composite ceramic plate is prepared by first preparing a composite raw material of boron carbide, high thermal conductivity nano-carbon fiber, and phenolic resin, which is then filled into a carbon fiber woven bag, sewn and cold-pressed to form a green billet, and then hot-pressed and sintered at a high temperature. However, the composite ceramic plate, the aramid fiber cloth, and the ultra-high molecular weight polyethylene back plate are bonded by a single epoxy resin adhesive, and the bonding effect is limited, which easily leads to a loose bonding between the layers of the bulletproof composite armor, thereby affecting the protective performance of the bulletproof composite armor; therefore, it is necessary to improve the material of the bulletproof armor to obtain a bulletproof armor with excellent protective performance. Summary of the invention

[0004] The purpose of the present invention is to provide a bulletproof composite armor and a preparation method thereof in view of the deficiencies in the prior art. Boron carbide is used as the main component. Modified basalt fiber and a composite binder composed of phenolic resin and silica sol are added to improve the mechanical properties of the ceramic bullet-facing surface layer. The ceramic bullet-facing surface layer / aramid III crack arrest cloth / ultra-high molecular weight polyethylene UD cloth are bonded between layers by a composite adhesive composed of epoxy resin and silica sol, which has a good bonding effect, can enhance the bonding force between layers, and improve the protective performance of the bulletproof composite armor.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0006] A bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a bullet-receiving surface layer.

[0007] Furthermore, the middle crack-stop layer is aramid III crack-stop cloth.

[0008] Furthermore, the back elastic surface layer is ultra-high molecular weight polyethylene UD cloth.

[0009] Furthermore, the ceramic bullet-facing surface layer is made by high-temperature hot-pressing and sintering 60-70 parts by weight of boron carbide, 15-20 parts by weight of silicon carbide, 8-10 parts by weight of modified basalt fiber, and 2-4 parts by weight of a composite binder.

[0010] Furthermore, the composite binder is composed of phenolic resin and silica sol in a mass ratio of 1:1-2.

[0011] In the technical solution of the present invention, the preparation method of the modified basalt fiber is:

[0012] S1. Add basalt fiber to Tris-HCl buffer, disperse evenly, add dopamine, stir evenly to obtain a mixed solution, transfer the mixed solution to a shaker, shake for 20-24 hours, filter, wash with water, and dry to obtain polydopamine-basalt fiber;

[0013] S2, adding polydopamine-basalt fiber to N,N-dimethylformamide, dispersing evenly, adding p-chloromethylbenzoic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 50-60° C. for 4-5 hours, filtering after the reaction is completed, washing with water and ethanol in turn, and drying to obtain functionalized basalt fiber;

[0014] S3. Add polyethylene glycol monomethyl ether and sodium hydride to anhydrous tetrahydrofuran, protect with nitrogen, stir and react at 30-40°C for 3-4h, add functionalized basalt fiber, continue to stir and react for 5-6h, after the reaction is completed, filter, wash with ethanol, and dry to obtain modified basalt fiber.

[0015] Furthermore, in step S1, the mass ratio of the basalt fiber to the Tris-HCl buffer is 1:10-15; the concentration of the Tris-HCl buffer is 10-15 mmol / L, and the pH value is 8.5-8.8; and the concentration of dopamine in the mixed solution is 2-3 mg / mL.

[0016] Furthermore, in step S2, the mass ratio of the polydopamine-basalt fiber, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N,N-dimethylformamide is 1:0.5-0.6:0.3-0.4:15-20.

[0017] Furthermore, in step S3, the mass ratio of the functionalized basalt fiber, polyethylene glycol monomethyl ether, sodium hydride, and anhydrous tetrahydrofuran is 1:0.6-0.8:0.2-0.3:15-20.

[0018] The invention uses basalt fiber as a raw material, firstly coats dopamine on the surface of the basalt fiber through oxidation-self-polymerization, then utilizes the amino group in the polydopamine structure on the surface to condense with p-chloromethylbenzoic acid under the action of condensation agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, introduces p-chloromethylbenzoic acid containing a rigid benzene ring onto the surface of the basalt fiber, and finally utilizes the chloromethyl group to react with polyethylene glycol monomethyl ether to introduce the polyethylene glycol monomethyl ether structure onto the surface of the basalt fiber to obtain the modified basalt fiber.

[0019] The present invention also provides a method for preparing a bulletproof composite armor, comprising the following steps:

[0020] (1) adding boron carbide, silicon carbide, modified basalt fiber, and a composite binder to water in proportion by weight, and mixing them evenly to obtain a ceramic slurry, vacuum drying, and crushing to obtain a ceramic powder, and pressing the ceramic powder into a shape to obtain a ceramic body;

[0021] (2) subjecting the ceramic body to high temperature hot pressing sintering, first at a pressure of 30-50 MPa and a temperature of 1800-2000°C for 1-2 hours, then at a pressure of 60-80 MPa and a temperature of 2000-2200°C for 0.5-1 hour, and after cooling, obtaining a ceramic anti-repellent surface layer;

[0022] (3) The surfaces of both sides of the aramid III crack-stop cloth are coated with composite glue, and then they are respectively laminated with a ceramic bullet-facing surface layer and an ultra-high molecular weight polyethylene UD cloth by hot pressing, and after cooling, a bullet-proof composite armor is obtained.

[0023] Furthermore, the particle size of the ceramic powder in step (1) is 250-300 mesh; during the pressing process, the pressure is 10-15 MPa and the time is 30-40 min.

[0024] Furthermore, the composite adhesive in step (3) is composed of epoxy resin and silica sol in a mass ratio of 1:1-2; the conditions for hot pressing composite are: pressure of 10-15MPa, temperature of 130-150°C, and time of 0.5-1h.

[0025] The present invention has the following beneficial effects:

[0026] 1. In order to enhance the mechanical properties of the ceramic bullet-proof surface layer, the present invention uses modified basalt fiber for modification of the ceramic bullet-proof surface layer. The polydopamine structure and rigid benzene ring on the surface of the modified basalt fiber can enhance the mechanical properties of the basalt fiber. The polyethylene glycol monomethyl ether structure with good dispersing effect can make the modified basalt fiber and other components evenly dispersed in the ceramic slurry, promote the mutual combination of the components, reduce the porosity, and thus improve the hardness, flexural strength and toughness of the ceramic.

[0027] 2. The present invention compounds phenolic resin and silica sol as a binder for the preparation of ceramic anti-bullet surface layer. The polydopamine structure on the surface of the modified basalt fiber has more hydroxyl groups, which interacts with the silica sol and can promote the gelation of the silica sol and the formation of a network structure, thereby improving the bonding effect, enhancing the density of the ceramic structure, and helping to improve the mechanical properties of the ceramic anti-bullet surface layer.

[0028] 3. The ceramic bullet-facing surface layer / aramid III crack-stop cloth / ultra-high molecular weight polyethylene UD cloth in the bullet-proof composite armor of the present invention are bonded between layers by a composite adhesive composed of epoxy resin and silica sol. The two are compounded to have a good bonding effect, can enhance the bonding force between layers, and improve the protective performance of the bullet-proof composite armor.

[0029] 4. The bulletproof composite armor prepared by the present invention has good low-temperature, high-temperature and wet-heat stability, can adapt to different environmental conditions, and has excellent protective performance. After effective shooting of 3 rounds of 54-type 12.7mm armor-piercing incendiary bullets, it was not penetrated, and the depression depth of the back bullet surface layer (ultra-high molecular weight polyethylene UD cloth) was less than 10mm, meeting the requirements of armor-piercing incendiary bullet protection. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] In the technical solution of the present invention, the chemical reagents used are all commercially available, including aramid III crack arrest cloth with a thickness of 1 mm; ultra-high molecular weight polyethylene UD cloth with a surface density of 16 kg / m 2 , thickness is 10mm; basalt fiber is nano-scale basalt fiber; solid content of silica sol is 40%; p-chloromethylbenzoic acid CAS No. 1642-81-5; 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride CAS No. 25952-53-8; sodium hydride CAS No. 7646-69-7; polyethylene glycol monomethyl ether CAS No. 9004-74-4 (average molecular weight is 1000); N,N-dimethylformamide CAS No. 68-12-2; ethanol CAS No. 64-17-5; anhydrous tetrahydrofuran CAS No. 109-99-9.

[0032] Embodiment 1

[0033] A bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a back-bullet surface layer; the intermediate crack-stop layer is aramid III crack-stop cloth; and the back-bullet surface layer is ultra-high molecular weight polyethylene UD cloth.

[0034] The ceramic bullet-proof surface layer is made by high-temperature hot-pressing sintering of 70 parts by weight of boron carbide, 18 parts by weight of silicon carbide, 10 parts by weight of modified basalt fiber, and 4 parts by weight of a composite binder; the composite binder is composed of phenolic resin and silica sol in a mass ratio of 1:2.

[0035] The preparation method of modified basalt fiber is:

[0036] S1. Add basalt fiber to Tris-HCl buffer, disperse evenly, add dopamine, stir evenly to obtain a mixed solution, transfer the mixed solution to a shaker, shake for 24 hours, filter, wash with water, and dry to obtain polydopamine-basalt fiber; wherein the mass ratio of basalt fiber to Tris-HCl buffer is 1:15; the concentration of Tris-HCl buffer is 15 mmol / L, and the pH value is 8.8; the concentration of dopamine in the mixed solution is 3 mg / mL;

[0037] S2, adding polydopamine-basalt fiber to N,N-dimethylformamide, dispersing evenly, adding p-chloromethylbenzoic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 60°C for 4 hours, filtering after the reaction is completed, washing with water and ethanol in turn, and drying to obtain functionalized basalt fiber; wherein the mass ratio of polydopamine-basalt fiber, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N,N-dimethylformamide is 1:0.6:0.4:20;

[0038] S3. Add polyethylene glycol monomethyl ether and sodium hydride to anhydrous tetrahydrofuran, protect with nitrogen, stir and react for 4 hours at 35°C, add functionalized basalt fiber, continue to stir and react for 6 hours. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified basalt fiber; wherein the mass ratio of functionalized basalt fiber, polyethylene glycol monomethyl ether, sodium hydride, and anhydrous tetrahydrofuran is 1:0.8:0.3:20.

[0039] A method for preparing a bulletproof composite armor comprises the following steps:

[0040] (1) Adding boron carbide, silicon carbide, modified basalt fiber and composite binder to water in proportion by weight, mixing evenly to obtain ceramic slurry, vacuum drying and crushing to obtain ceramic powder, pressing the ceramic powder into a shape to obtain a ceramic body; wherein the particle size of the ceramic powder is 300 mesh; during the pressing process, the pressure is 15 MPa and the time is 35 min;

[0041] (2) The ceramic body is subjected to high-temperature hot pressing sintering, first at a pressure of 40 MPa and a temperature of 2000°C for 1.5 h, then at a pressure of 80 MPa and a temperature of 2100°C for 1 h, and after cooling, a ceramic anti-bullet surface layer with a thickness of 9 mm is obtained;

[0042] (3) The composite adhesive is coated on both sides of the aramid III crack-stop cloth, and then it is laminated with a ceramic bullet-facing surface layer and an ultra-high molecular weight polyethylene UD cloth by hot pressing. After cooling, a bulletproof composite armor is obtained; the composite adhesive is composed of epoxy resin and silica sol in a mass ratio of 1:2; the conditions for hot pressing and laminating are: pressure of 15 MPa, temperature of 140°C, and time of 1 h.

[0043] Embodiment 2

[0044] A bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a back-bullet surface layer; the intermediate crack-stop layer is aramid III crack-stop cloth; and the back-bullet surface layer is ultra-high molecular weight polyethylene UD cloth.

[0045] The ceramic bullet-proof surface layer is made by high-temperature hot-pressing sintering of 65 parts by weight of boron carbide, 20 parts by weight of silicon carbide, 9 parts by weight of modified basalt fiber, and 3 parts by weight of a composite binder; the composite binder is composed of phenolic resin and silica sol in a mass ratio of 1:1.5.

[0046] The preparation method of modified basalt fiber is:

[0047] S1. Add basalt fiber to Tris-HCl buffer, disperse evenly, add dopamine, stir evenly to obtain a mixed solution, transfer the mixed solution to a shaker, shake for 20 hours, filter, wash with water, and dry to obtain polydopamine-basalt fiber; wherein the mass ratio of basalt fiber to Tris-HCl buffer is 1:10; the concentration of Tris-HCl buffer is 10 mmol / L, and the pH value is 8.5; the concentration of dopamine in the mixed solution is 2.5 mg / mL;

[0048] S2, adding polydopamine-basalt fiber to N,N-dimethylformamide, dispersing evenly, adding p-chloromethylbenzoic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 50°C for 5 hours, filtering after the reaction is completed, washing with water and ethanol in turn, and drying to obtain functionalized basalt fiber; wherein the mass ratio of polydopamine-basalt fiber, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N,N-dimethylformamide is 1:0.55:0.3:15;

[0049] S3. Add polyethylene glycol monomethyl ether and sodium hydride to anhydrous tetrahydrofuran, protect with nitrogen, stir and react for 3 hours at 40°C, add functionalized basalt fiber, continue to stir and react for 5.5 hours. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified basalt fiber; wherein the mass ratio of functionalized basalt fiber, polyethylene glycol monomethyl ether, sodium hydride, and anhydrous tetrahydrofuran is 1:0.7:0.2:15.

[0050] A method for preparing a bulletproof composite armor comprises the following steps:

[0051] (1) Adding boron carbide, silicon carbide, modified basalt fiber and composite binder to water in proportion by weight, mixing evenly to obtain ceramic slurry, vacuum drying and crushing to obtain ceramic powder, pressing the ceramic powder into a shape to obtain a ceramic body; wherein the particle size of the ceramic powder is 275 mesh; during the pressing and molding, the pressure is 10 MPa and the time is 40 min;

[0052] (2) subjecting the ceramic body to high-temperature hot pressing sintering, first at a pressure of 50 MPa and a temperature of 1900°C for 1 hour, then at a pressure of 70 MPa and a temperature of 2200°C for 0.5 hour, and after cooling, a ceramic anti-bullet surface layer with a thickness of 10 mm is obtained;

[0053] (3) Composite adhesive is coated on both sides of the aramid III crack-stop cloth, and then it is laminated with a ceramic bullet-facing surface layer and an ultra-high molecular weight polyethylene UD cloth by hot pressing. After cooling, a bulletproof composite armor is obtained; the composite adhesive is composed of epoxy resin and silica sol in a mass ratio of 1:1.5; the conditions for hot pressing and laminating are: pressure of 13 MPa, temperature of 130 °C, and time of 0.8 h.

[0054] Embodiment 3

[0055] A bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a back-bullet surface layer; the intermediate crack-stop layer is aramid III crack-stop cloth; and the back-bullet surface layer is ultra-high molecular weight polyethylene UD cloth.

[0056] The ceramic bullet-proof surface layer is made by high-temperature hot-pressing sintering of 60 parts by weight of boron carbide, 15 parts by weight of silicon carbide, 8 parts by weight of modified basalt fiber, and 2 parts by weight of a composite binder; the composite binder is composed of phenolic resin and silica sol in a mass ratio of 1:1.

[0057] The preparation method of modified basalt fiber is:

[0058] S1. Add basalt fiber to Tris-HCl buffer, disperse evenly, add dopamine, stir evenly to obtain a mixed solution, transfer the mixed solution to a shaker, shake for 22 hours, filter, wash with water, and dry to obtain polydopamine-basalt fiber; wherein the mass ratio of basalt fiber to Tris-HCl buffer is 1:13; the concentration of Tris-HCl buffer is 12 mmol / L, and the pH value is 8.6; the concentration of dopamine in the mixed solution is 2 mg / mL;

[0059] S2, adding polydopamine-basalt fiber to N,N-dimethylformamide, dispersing evenly, adding p-chloromethylbenzoic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 55°C for 4.5 hours, filtering after the reaction is completed, washing with water and ethanol in turn, and drying to obtain functionalized basalt fiber; wherein the mass ratio of polydopamine-basalt fiber, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N,N-dimethylformamide is 1:0.5:0.35:18;

[0060] S3. Add polyethylene glycol monomethyl ether and sodium hydride to anhydrous tetrahydrofuran, protect with nitrogen, stir and react for 3.5 hours at 30°C, add functionalized basalt fiber, continue to stir and react for 5 hours. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified basalt fiber; wherein the mass ratio of functionalized basalt fiber, polyethylene glycol monomethyl ether, sodium hydride, and anhydrous tetrahydrofuran is 1:0.6:0.25:18.

[0061] A method for preparing a bulletproof composite armor comprises the following steps:

[0062] (1) Adding boron carbide, silicon carbide, modified basalt fiber and composite binder to water in proportion by weight, mixing evenly to obtain ceramic slurry, vacuum drying and crushing to obtain ceramic powder, pressing the ceramic powder into a shape to obtain a ceramic body; wherein the particle size of the ceramic powder is 250 mesh; during the pressing and molding, the pressure is 13 MPa and the time is 30 min;

[0063] (2) The ceramic body is subjected to high-temperature hot pressing sintering, first at a pressure of 30 MPa and a temperature of 1800°C for 2 h, then at a pressure of 60 MPa and a temperature of 2000°C for 0.8 h, and after cooling, a ceramic anti-bullet surface layer with a thickness of 12 mm is obtained;

[0064] (3) Composite adhesive is coated on both sides of the aramid III crack-stop cloth, and then it is laminated with a ceramic bullet-facing surface layer and an ultra-high molecular weight polyethylene UD cloth by hot pressing. After cooling, a bulletproof composite armor is obtained; the composite adhesive is composed of epoxy resin and silica sol in a mass ratio of 1:1; the conditions for hot pressing and laminating are: pressure of 10 MPa, temperature of 150°C, and time of 0.5 h.

[0065] Comparative Example 1

[0066] Compared with Example 1, the modified basalt fiber in the ceramic bullet-facing surface layer is replaced with basalt fiber in this comparative example.

[0067] A bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a back-bullet surface layer; the intermediate crack-stop layer is aramid III crack-stop cloth; and the back-bullet surface layer is ultra-high molecular weight polyethylene UD cloth.

[0068] The ceramic bullet-proof surface layer is made of 70 parts by weight of boron carbide, 18 parts by weight of silicon carbide, 10 parts by weight of basalt fiber and 4 parts by weight of a composite binder through high-temperature hot pressing and sintering; the composite binder is composed of phenolic resin and silica sol in a mass ratio of 1:2.

[0069] A method for preparing a bulletproof composite armor comprises the following steps:

[0070] (1) Adding boron carbide, silicon carbide, basalt fiber, and a composite binder to water according to a weight ratio, and mixing them evenly to obtain a ceramic slurry, vacuum drying, and crushing to obtain a ceramic powder, and pressing the ceramic powder into a shape to obtain a ceramic body; wherein the particle size of the ceramic powder is 300 meshes; during the pressing process, the pressure is 15 MPa, and the time is 35 min;

[0071] (2) Same as step (2) of Example 1;

[0072] (3) Same as step (3) of Example 1.

[0073] Comparative Example 2

[0074] Compared with Example 1, the composite binder in the ceramic bullet-proof surface layer is replaced with phenolic resin in this comparative example.

[0075] A bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a back-bullet surface layer; the intermediate crack-stop layer is aramid III crack-stop cloth; and the back-bullet surface layer is ultra-high molecular weight polyethylene UD cloth.

[0076] The ceramic bullet-facing surface layer is made of 70 parts by weight of boron carbide, 18 parts by weight of silicon carbide, 10 parts by weight of modified basalt fiber and 4 parts by weight of phenolic resin through high-temperature hot pressing sintering.

[0077] The preparation method of the modified basalt fiber is the same as that of Example 1.

[0078] A method for preparing a bulletproof composite armor comprises the following steps:

[0079] (1) Adding boron carbide, silicon carbide, modified basalt fiber and phenolic resin to water in proportion by weight, mixing evenly to obtain ceramic slurry, vacuum drying and crushing to obtain ceramic powder, pressing the ceramic powder into a shape to obtain a ceramic body; wherein the particle size of the ceramic powder is 300 mesh; during the pressing process, the pressure is 15 MPa and the time is 35 min;

[0080] (2) Same as step (2) of Example 1;

[0081] (3) Same as step (3) of Example 1.

[0082] Comparative Example 3

[0083] Compared with Example 1, the modified basalt fiber in the ceramic bullet-proof surface layer is replaced by basalt fiber, and the composite binder is replaced by phenolic resin.

[0084] A bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a back-bullet surface layer; the intermediate crack-stop layer is aramid III crack-stop cloth; and the back-bullet surface layer is ultra-high molecular weight polyethylene UD cloth.

[0085] The ceramic bullet-facing surface layer is made of 70 parts by weight of boron carbide, 18 parts by weight of silicon carbide, 10 parts by weight of basalt fiber and 4 parts by weight of phenolic resin through high-temperature hot-pressing sintering.

[0086] A method for preparing a bulletproof composite armor comprises the following steps:

[0087] (1) Adding boron carbide, silicon carbide, basalt fiber and phenolic resin to water according to a weight ratio, mixing evenly to obtain a ceramic slurry, vacuum drying and crushing to obtain a ceramic powder, and pressing the ceramic powder to obtain a ceramic body; wherein the particle size of the ceramic powder is 300 mesh; during the pressing process, the pressure is 15 MPa and the time is 35 min;

[0088] (2) Same as step (2) of Example 1;

[0089] (3) Same as step (3) of Example 1.

[0090] Comparative Example 4

[0091] Compared with Example 1, this comparative example replaces the composite glue in step (3) of the method for preparing the bulletproof composite armor with epoxy resin.

[0092] A bulletproof composite armor comprises a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a back-bullet surface layer; the intermediate crack-stop layer is aramid III crack-stop cloth; and the back-bullet surface layer is ultra-high molecular weight polyethylene UD cloth.

[0093] The ceramic bullet-proof surface layer is made by high-temperature hot-pressing sintering of 70 parts by weight of boron carbide, 18 parts by weight of silicon carbide, 10 parts by weight of modified basalt fiber, and 4 parts by weight of a composite binder; the composite binder is composed of phenolic resin and silica sol in a mass ratio of 1:2.

[0094] The preparation method of the modified basalt fiber is the same as that of Example 1.

[0095] A method for preparing a bulletproof composite armor comprises the following steps:

[0096] (1) Same as step (1) of Example 1;

[0097] (2) Same as step (2) of Example 1;

[0098] (3) Epoxy resin is coated on both sides of the aramid III crack-stop cloth, and then the surfaces are respectively laminated with a ceramic bullet-facing surface layer and an ultra-high molecular weight polyethylene UD cloth by hot pressing. After cooling, a bulletproof composite armor is obtained; the conditions for hot pressing and laminating are: pressure of 15 MPa, temperature of 140°C, and time of 1 h.

[0099] 1. Performance test of ceramic anti-bullet surface

[0100] The performance tests were carried out on the ceramic anti-ballistic surface layers prepared in Examples 1 to 3 and Comparative Examples 1 to 3, wherein the hardness was measured according to GB / T 16534-2009, the bending strength was measured according to GB / T 6569-2006, and the fracture toughness was measured according to GB / T23806-2009. The results are shown in Table 1.

[0101] Table 1

[0102]

[0103] From the results in Table 1, it can be seen that the hardness, flexural strength and toughness of the ceramic anti-bullet surface layer prepared in Examples 1 to 3 are significantly higher than those in Comparative Examples 1 to 3, indicating that the ceramic anti-bullet surface layer provided by the present invention has excellent mechanical properties. Compared with Comparative Examples 1 to 3, in Example 1 of the present invention, modified basalt fiber and a composite binder composed of phenolic resin and silica sol are used to prepare the ceramic anti-bullet surface layer, wherein the polydopamine structure and rigid benzene ring on the surface of the modified basalt fiber can enhance the mechanical properties of the basalt fiber, and the polyethylene glycol monomethyl ether structure with good dispersing effect on its surface can make the modified basalt fiber and other components evenly dispersed in the ceramic slurry, promote the mutual combination of the components, reduce the porosity, and thus improve the hardness, flexural strength and toughness of the ceramic; the present invention uses a compound of phenolic resin and silica sol as a binder, and the polydopamine structure contains more hydroxyl groups, which interact with the silica sol to promote the gelation of the silica sol and the formation of a network structure, thereby improving the bonding effect, enhancing the density of the ceramic structure, and further contributing to improving the mechanical properties of the ceramic.

[0104] 2. Performance test of bulletproof composite armor

[0105] The stability and protective performance tests of the bulletproof composite armors prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were performed. The stability test included a low temperature test, a high temperature test and a wet heat test. The low temperature test was performed according to the GJB 150.4A-2009 standard, with the conditions of -45°C and 144h; the high temperature test was performed according to the GJB 150.3A-2009 standard, with the conditions of 70°C and 96h; the wet heat test was performed according to the temperature and humidity specified in Article 4.3.3 of the GJB 150.9A-2009 standard, with a total of 10 cycles; the protective performance was performed according to the GJB 59.18-88 standard, under normal temperature and humidity conditions, after effective shooting of 3 rounds of 54-type 12.7mm armor-piercing incendiary bullets with a bullet speed of 820m / s, observe whether the bullet-proof composite armor is penetrated and the depth of the depression of the back bullet surface layer (ultra-high molecular weight polyethylene UD cloth). The results are shown in Table 2 below, where √ represents that the sample has no bubbling, cracking, delamination, deformation, and scratches, and × represents that the sample has any one or more of bubbling, cracking, delamination, deformation, and scratches.

[0106] Table 2

[0107]

[0108] From the results in Table 2, it can be seen that the bulletproof composite armor prepared in Examples 1 to 3 has good low-temperature, high-temperature and wet-heat stability, no bubbling, no cracking, no delamination, no deformation, and no scratches. Moreover, the bulletproof composite armor provided by the present invention has excellent protective performance. After effective shooting of 3 54-type 12.7mm armor-piercing incendiary bullets, it was not penetrated, and the depression depth of the back bullet surface layer (ultra-high molecular weight polyethylene UD cloth) was less than 10 mm, which met the requirements of armor-piercing incendiary bullets. Compared with Comparative Examples 1 to 4, the present invention uses a ceramic bullet-facing surface layer with excellent mechanical properties for bullet-proof composite armor, and the protective effect is better. In the bullet-proof composite armor of the present invention, the ceramic bullet-facing surface layer / aramid III crack-stop cloth / ultra-high molecular weight polyethylene UD cloth are bonded between layers by a composite glue composed of epoxy resin and silica sol. The two are compounded, have a good bonding effect, can enhance the bonding force between layers, and help to improve the protective performance of the bullet-proof composite armor.

[0109] It should be noted that, in this document, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device; although the embodiments of the present application have been shown and described, it can be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A bulletproof composite armor, comprising a ceramic bullet-facing surface layer, an intermediate crack-stop layer and a back-bullet surface layer, characterized in that: The ceramic anti-bullet surface layer is made by high-temperature hot-pressing sintering of 60-70 parts by weight of boron carbide, 15-20 parts by weight of silicon carbide, 8-10 parts by weight of modified basalt fiber, and 2-4 parts by weight of a composite binder; The preparation method of the modified basalt fiber is: S1. Add basalt fiber to Tris-HCl buffer, disperse evenly, add dopamine, stir evenly to obtain a mixed solution, transfer the mixed solution to a shaker, shake for 20-24 hours, filter, wash with water, and dry to obtain polydopamine-basalt fiber; S2, adding polydopamine-basalt fiber to N,N-dimethylformamide, dispersing evenly, adding p-chloromethylbenzoic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 50-60° C. for 4-5 hours, filtering after the reaction is completed, washing with water and ethanol in turn, and drying to obtain functionalized basalt fiber; S3. Add polyethylene glycol monomethyl ether and sodium hydride to anhydrous tetrahydrofuran, protect with nitrogen, stir and react at 30-40°C for 3-4h, add functionalized basalt fiber, continue to stir and react for 5-6h, after the reaction is completed, filter, wash with ethanol, and dry to obtain modified basalt fiber.

2. The bulletproof composite armor according to claim 1, characterized in that: The composite binder consists of phenolic resin and silica sol in a mass ratio of 1:1-2.

3. The bulletproof composite armor according to claim 1, characterized in that: The mass ratio of the basalt fiber to the Tris-HCl buffer in step S1 is 1:10-15; the concentration of the Tris-HCl buffer is 10-15 mmol / L, and the pH value is 8.5-8.8; and the concentration of dopamine in the mixed solution is 2-3 mg / mL.

4. The bulletproof composite armor according to claim 1, characterized in that: The mass ratio of the polydopamine-basalt fiber, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N,N-dimethylformamide in step S2 is 1:0.5-0.6:0.3-0.4:15-20.

5. The bulletproof composite armor according to claim 1, characterized in that: The mass ratio of the functionalized basalt fiber, polyethylene glycol monomethyl ether, sodium hydride and anhydrous tetrahydrofuran in step S3 is 1:0.6-0.8:0.2-0.3:15-20.

6. The bulletproof composite armor according to claim 1, characterized in that: The middle crack-stopping layer is aramid III crack-stopping cloth.

7. The bulletproof composite armor according to claim 1, characterized in that: The back elastic surface layer is ultra-high molecular weight polyethylene UD cloth.

8. A method for preparing a bulletproof composite armor according to any one of claims 1 to 7, characterized in that: The steps include: (1) adding boron carbide, silicon carbide, modified basalt fiber, and a composite binder to water in proportion by weight, and mixing them evenly to obtain a ceramic slurry, vacuum drying, and crushing to obtain a ceramic powder, and pressing the ceramic powder into a shape to obtain a ceramic body; (2) subjecting the ceramic body to high temperature hot pressing sintering, first at a pressure of 30-50 MPa and a temperature of 1800-2000°C for 1-2 hours, then at a pressure of 60-80 MPa and a temperature of 2000-2200°C for 0.5-1 hour, and after cooling, obtaining a ceramic anti-repellent surface layer; (3) The surfaces of both sides of the aramid III crack-stop cloth are coated with composite glue, and then they are respectively laminated with a ceramic bullet-facing surface layer and an ultra-high molecular weight polyethylene UD cloth by hot pressing, and after cooling, a bullet-proof composite armor is obtained.

9. The method for preparing a bulletproof composite armor according to claim 8, characterized in that: The particle size of the ceramic powder in step (1) is 250-300 mesh; during the pressing process, the pressure is 10-15 MPa and the time is 30-40 min.

10. The method for preparing a bulletproof composite armor according to claim 8, characterized in that: The composite adhesive in step (3) is composed of epoxy resin and silica sol in a mass ratio of 1:1-2; the conditions for hot pressing composite are: pressure of 10-15MPa, temperature of 130-150°C, and time of 0.5-1h.

Citation Information

Patent Citations

  • Bulletproof composite armor and preparation method thereof

    CN111319318A

  • Bulletproof ceramic composite armor and preparation method thereof

    CN111361230A

  • Continuous basalt fiber reinforced ceramic composite and preparation method for same

    CN102701770A

  • Basalt composite bulletproof plate with high impact resistance

    CN110006291A